Study the effect of particle on surface of a coaxial electrode system - 239995 Haryanty Mat Jusoh (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2006